Selected Age Management Practices in the Assessment of Older Employees - Lubrańska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The aging of labor resources is of interest to demographers, economists, representatives of social sciences, organizations and management. Among the solutions to the problem, the idea of age management draws attention. It is an element of human resource management, favors the effective use of individual potential, opportunities, and competences of employees, while maintaining the value of age diversity. The main objective of the research was to assess the frequency of using age management practices in Polish companies, seen from the perspective of older employees. Employees in late adulthood (n = 243), aged 56–78, participated in the study. An own questionnaire was used on: professional development and training, training policy, health protection and promotion, employment flexibility, ergonomics and safety at work, retirement‑related policy. The respondents in their companies gave the highest ratings for efforts to ensure work safety, risk control, and the lowest for activities related to the retirement‑related policy.